Pathophysiology and management of risperidone-induced sialorrhea: case report - Torrico, Tyler; Kahlon, Angad (Frontiers in Psychiatry, 2023)
Background Among antipsychotics, sialorrhea is most associated with clozapine, and when it occurs, it is uncomfortable, socially stigmatizing, and can contribute to medication non-adherence. Risperidone has a generally negligible muscarinic activity compared to clozapine, and yet, multiple reports of severe sialorrhea associated with risperidone have been reported. Case presentation This case report describes risperidone-induced sialorrhea that was unintentionally masked by simultaneous clonidine administration that was intended to treat hypertension. Interestingly, sialorrhea was present but mild when clonidine was present; however, when risperidone was further titrated and clonidine removed, a significant worsening of sialorrhea developed. Sialorrhea did not respond to treatment with anticholinergic medication. Conclusion The pathophysiology of antipsychotic-induced sialorrhea is complex and varies between antipsychotics. Risperidone-induced sialorrhea is suspected of having prominent adrenergic pathophysiology that is likely composed of highly viscoelastic saliva (high protein content), differing from the more commonly encountered clozapine-induced sialorrhea. Risperidone-induced sialorrhea is reported as more likely to respond to dose reduction and treatment with α2-adrenergic receptor agonists or β-adrenergic receptor antagonists and less likely to respond to anticholinergic (antimuscarinic) medications.